Pengaruh Perubahan Temperatur Udara Luar pada Kinerja Pengkondisi Udara Direct Expansion System - Akmal Fadhillah Muslim; Sumeru; Nani Yuningsih (Prosiding Industrial Research Workshop and National Seminar, 2025)
Outdoor air conditions, particularly temperature, are important factors that significantly influence the performance of air conditioning systems in buildings. Fluctuations in outdoor temperature can increase the cooling load and energy consumption of HVAC systems, especially in Direct Expansion (DX) systems commonly used in Air Handling Units (AHU). This study aims to analyze the impact of outdoor temperature changes on the performance of DX-type AHUs. The data collection involved measuring outdoor air temperature, refrigerant temperature and pressure, supply air temperature, electrical power consumption, and calculating the Coefficient of Performance (COP). Measurements were taken in the morning, noon, and afternoon. The results showed that the cooling capacity decreased by 1.274 kW as outdoor temperature rose from 26.25°C to 29.29°C, with an average reduction of 0.44 kW per 1°C. Beyond this range, the cooling capacity stabilized around 30.010 kW. The system’s power input increased by 0.975 kW within the temperature range of 26.25°C to 31.61°C, equivalent to an average increase of 0.182 kW per 1°C. The actual COP declined by a total of 0.29 over the same range, averaging a decrease of 0.05 per 1°C rise in outdoor temperature. These findings indicate that outdoor temperature has a significant effect on the cooling capacity, energy consumption, and Coefficient of Performance DX AHU systems.